An Application for Medical Diagnosis Using Correlation Coefficient With Modal Operators and Operator Identifying and Unary - Bertei, Alex; Reiser, Renata H. S.; Foss, Luciana (Anais do Workshop-Escola de Informática Teórica (WEIT), 2021)
This paper aims to study the Atanassov's correlation coefficient (A-CC) between two of Atanassov's intuitionistic fuzzy sets (A-IFS), obtained as images of intuitionistic fuzzy modal operators. The composition of modal operators are investigated, verifying under which conditions an A-CC preserves the main properties related to conjugate and complement operations performed on A-IFS. In addition, a simulation based on the proposal methodology using operators described above is applied to a medical diagnosis analysis.